2017
DOI: 10.5114/biolsport.2017.65339
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine responses and acute mTOR pathway phosphorylation to resistance exercise with leucine and whey

Abstract: Leucine ingestion reportedly activates the mTOR pathway in skeletal muscle, contributing to a hypertrophy response. The purpose of the study was to compare the post-resistance exercise effects of leucine and whey protein supplementation on endocrine responses and muscle mTOR pathway phosphorylation. On visit 1, subjects (X±SD; n=20; age=27.8±2.8yrs) provided baseline blood samples for analysis of cortisol, glucose and insulin; a muscle biopsy of the vastus lateralis muscle to assess mTOR signaling pathway phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
15
0
5
Order By: Relevance
“…It is striking that the composition of the animals’ diet was high in protein (23%), which is a key factor in inducing muscle growth. It is well recognized that a positive nitrogen balance deriving from a protein source with a good proportion of essential amino acids, particularly leucine, creates, together with other elements, an anabolic environment for growing muscle mass [ 73 ]. Additionally, SM has come to be recognized as a protein synthesis stimulator, because it is able to enter the nucleus and enhance DNA synthesis, along with the transcription of rRNA, by stimulating RNA polymerase I enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that the composition of the animals’ diet was high in protein (23%), which is a key factor in inducing muscle growth. It is well recognized that a positive nitrogen balance deriving from a protein source with a good proportion of essential amino acids, particularly leucine, creates, together with other elements, an anabolic environment for growing muscle mass [ 73 ]. Additionally, SM has come to be recognized as a protein synthesis stimulator, because it is able to enter the nucleus and enhance DNA synthesis, along with the transcription of rRNA, by stimulating RNA polymerase I enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Beside thorough sleep and dietary habits instructions, a post-training recovery drink containing whey protein and maltodextrin was provided after every session to all participants for a better control of nutrient intake and timing, except for the acute resistance loading protocol with muscle biopsy. It has been shown that supplementation of whey protein before and/or immediately after heavy resistance exercise increases anabolic signalling in human skeletal muscle (Hulmi et al 2009, Lane et al 2017). However, data on signalling pathways involved in skeletal muscle hypertrophy support the possibility of hypertrophic adaptations being time-of-day-dependent.…”
Section: Skeletal Muscle Strength and Hypertrophymentioning
confidence: 99%
“…Leucine modulates protein synthesis by increasing post-transcription efficiency, enhancing the translation rate of mRNAs ( Kimball and Jefferson, 2006 ; Wilkinson et al, 2017 ). The mechanism of synthesis is due to phosphorylation of the protein kinase p70S6k, which induces the phosphorylation of the ribosomal protein (S6), the eukaryotic initiation factor (eIF4B) and a protein involved in stretching the translation process, Eukaryotic elongation factor kinase 2 (eEF2k), which affects the initiation and elongation of other mRNA classes ( Ananieva et al, 2016 ; Lane et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%